Durable response for ampullary and duodenal adenocarcinoma with a nab‐paclitaxel plus gemcitabine ± cisplatin combination - Putao Cen; Curtis J. Wray; Songlin Zhang; Nirav C. Thosani; Brian Cuong Dinh; Anneliese Gonzalez; Virginia Mohlere; John Steven Bynon (Cancer Medicine, 2019)
Abstract Background/Aim There is no standard salvage chemotherapy for metastatic periampullary adenocarcinoma and duodenal adenocarcinoma and the prognosis of those who fail oxaliplatin, irinotecan, and 5FU is dismal. We examined nanoparticle albumin‐bound paclitaxel (nab‐paclitaxel) as salvage therapy for these two malignancies. Methods Patients who failed oxaliplatin, irinotecan, and 5FU and whose archival tumors stained immunohistochemical (IHC) tumor positive for CK7 or MUC1 received nab‐paclitaxel and gemcitabine therapy with or without cisplatin. Results Three patients, 2 with metastatic ampullary adenocarcinoma and 1 with duodenal adenocarcinoma with positive IHC staining for CK7 or MUC1 who failed 2 lines of chemotherapy with oxaliplatin, irinotecan, and 5FU received nab‐paclitaxel and gemcitabine with or without cisplatin. All achieved excellent tumor response on CT scans with marked falls in tumor markers CA19‐9 and CEA as well as ≥1 year of progression‐free survival. All 3 have continued to survive 2‐3 years since diagnosed with stage 4 metastatic adenocarcinoma. Conclusions Nab‐paclitaxel plus gemcitabine with or without cisplatin should be investigated as a standard‐of‐care chemotherapy regimen for patients with ampullary adenocarcinoma and duodenal adenocarcinoma.